Do faces and body postures integrate similarly for distinct emotions, kinds of emotion and judgent dimensions? (2016)
Faces and bodies are typically seen together in most social interactions, rendering probable that facial and bodily expressions are perceived and eventually processed simultaneously. The methodology of Information Integration Theory and Functional Measurement was used here to address the following questions: Under what rules do facial and bodily information integrate in judgments over different dimensions of so-called basic and self-conscious emotions? How does relative importance of face and body vary across emotions and judgment dimensions? Does the relative importance of face and body afford a basis for distinguishing between basic and self-conscious emotions? Three basic (happiness, anger, sadness) and two social self-conscious emotions (shame and pride) were considered in this study. Manipulated factors were 3-D realistic facial expressions (varied across 5 levels of intensity) and synthetic 3-D realistic body postures (3 levels of intensity). Different groups of participants judged expressed intensity, valence, or arousal of the combined presentations of face and body, meaning that judgment dimension was varied between-subjects. With the exception of arousal judgments, averaging was the predominant integration rule. Relative importance of face and body was found to vary as a function of judgment dimension, specific emotions and, for judgments of arousal only, type of emotion (basic versus self-conscious).